2008
DOI: 10.2522/ptj.20070145
|View full text |Cite
|
Sign up to set email alerts
|

Movement Training Advances the Emergence of Reaching in Infants Born at Less Than 33 Weeks of Gestational Age: A Randomized Clinical Trial

Abstract: This project demonstrates that there are early gross motor skill differences in infants born at less than 33 weeks of gestational age. A caregiver-based daily training program, however, is effective at lessening some, but not all, of these differences over the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
136
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(148 citation statements)
references
References 106 publications
7
136
0
5
Order By: Relevance
“…In short term physical therapy treatments based on the administration of sensoriperceptive techniques 31) , and the stimulation of motor development using active and passive techniques 29) , infants showed improved motor performance. It is interesting to highlight the results obtained by Heathcock et al 27) who reported the earliness in the emergence of reaching in preterm infants after a training programme. In the medium term studies by Goodman et al 26) and from Rothberg et al 32) reported favourable results for Bobath method, after initiating the intervention in the hospital and continuing it at home.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In short term physical therapy treatments based on the administration of sensoriperceptive techniques 31) , and the stimulation of motor development using active and passive techniques 29) , infants showed improved motor performance. It is interesting to highlight the results obtained by Heathcock et al 27) who reported the earliness in the emergence of reaching in preterm infants after a training programme. In the medium term studies by Goodman et al 26) and from Rothberg et al 32) reported favourable results for Bobath method, after initiating the intervention in the hospital and continuing it at home.…”
Section: Discussionmentioning
confidence: 84%
“…It is important to point out that 5 of the16 studies used in this review had high methodological quality, a score of six or higher on the PEDro scale, 15,25,[29][30][31] five had medium methodological quality, a score of five, 20,22,26,27,33) and six had low methodological quality, with scores of less five, 21,23,24,28,32,34) . Two out of five studies with high methodological quality reported favourable results for the intervention groups 15,29) (40%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Reaching training delivered by caregivers to their preterm infants was able to partially ameliorate the delayed reaching skills often observed in the preterm population. 18 Similarly, training parents to practice specific motor tasks with typically developing infants accelerated the rate of motor development in both the short and long term. 19,20 In the small amount of literature about the benefits of EE for infants at risk for brain injury, we know that premature infants demonstrate neurobehavioral benefits from sensory-specific EE activities, such as massage 21 26,27 Because only ∼8% to 15% of premature infants will go on to have CP, 28 it is not clear whether interventions aimed at preterm infants will have clear benefits for infants with CP.…”
Section: Methodsmentioning
confidence: 99%
“…13,108 With emerging research investigating early intervention for infants (younger than three years) at risk of hemiplegia, (e.g. 9,58,109 ) the efficacy of existing non-surgical UL interventions for this younger, at-risk population is unclear.…”
Section: Introductionmentioning
confidence: 99%